Posttraumatic Stress Disorder, Adverse Childhood Events, and Buccal Cell Telomere Length in Elderly Swiss Former Indentured Child Laborers - Küffer, Andreas Lorenz; O’Donovan, Aoife; Burri, Andrea; Maercker, Andreas (Frontiers in Psychiatry, 2016)
Posttraumatic stress disorder (PTSD) is associated with increased risk for age-related diseases and early mortality. Accelerated biological aging could contribute to this elevated risk. The aim of the present study was to assess buccal cell telomere length (BTL) – a proposed marker of biological age – in men and women with and without PTSD. The role of childhood trauma was assessed as a potential additional risk factor for shorter TL. The sample included 62 former indentured Swiss child laborers (age: M=76.19, SD=6.18) and 58 healthy controls (age: M=71.85, SD=5.97). Structured clinical interviews were conducted to screen for PTSD and other psychiatric disorders. The Childhood Trauma Questionnaire (CTQ) was used to assess childhood trauma exposure. Quantitative polymerase chain reaction was used to measure BTL. Covariates include age, sex, years of education, self-evaluated financial situation, depression, mental-, and physical functioning. Forty-eight (77.42%) of the former indentured child laborers screened positive for childhood trauma and 21 (33.87%) had partial or full-blown PTSD. Results did not support our hypotheses that PTSD and childhood trauma would be associated with shorter BTL. In fact, results revealed a trend towards longer BTL in participants with partial or full PTSD (F(2,109) = 3.27, p = .04, η2 = 0.06), and longer BTL was marginally associated with higher CTQ scores (age adjusted: β = 0.17 [95% CI: -0.01 – 0.35], t = 1.90, p = .06). Furthermore, within-group analyses indicated no significant association between BTL and CTQ scores. To our knowledge this is the first study exploring the association between childhood trauma and BTL in older individuals with and without PTSD. Contrary to predictions, there were no significant differences in BTL between participants with and without PTSD in our adjusted analyses and childhood adversity was not associated with BTL. Possible explanations and future research possibilities are discussed.